Identification of the Vibration Environment of Railway Infrastructure - Burdzik, Rafał; Nowak, Bogusław (Procedia engineering, 2017)
The subject matter of vibrations in railway transport is still an ongoing cognitive issue. In terms of an increase of speed, size, as well as weight of rail vehicles, the scale of effects of vibrations generated when a train moves also grows. However, the authors decided to conduct research and analyze vibrations in a different approach. The article presents the results of the research which aim was to identify the vibration environment of the railway infrastructure. In order to do this, the research on a test track equipped with typical devices of the railway infrastructure, such as crossing signaling devices, point machines was conducted. Additionally, certain experiments were conducted in the environment of other railway occurrences as result of which vibrations are generated. Experiments of a vehicle passage through a level crossing were performed and a passage of a light rail vehicle in a form of a two-axle bogie was simulated. This research aims at analyzing the forms and distributions of vibrations in respect of a possibility to separate signals in the actual environment in which they occur and where often several forced vibrations overlap.